Preparation and Structure of 1,6-Diphenyldispiro[2.1.2.1]octane-4,8-dione - Voss, Jürgen; Röske, Rüdiger; Adiwidjaja, Gunadi (Letters in Organic Chemistry, 2019)
The dimerization of 1-bromo-2-phenylcyclopropanecarbonyl chloride by the use of the zinc/copper couple selectively leads to anti-trans-1,6-diphenyldispiro[2.1.2.1]octane-4,8-dione, the structure and configuration of which are proved by X-ray structure analysis.
Keywords: X-Ray structure